2011
DOI: 10.3109/00498254.2011.617848
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and pharmacokinetics of S-propargyl-L-cysteine, a novel cardioprotective agent, after single and multiple doses in Beagle dogs

Abstract: As a novel hydrogen sulfide-modulated agent, S-propargyl-L-cysteine (SPRC) is proven to be a potent cardioprotective candidate. Bioavailability and pharmacokinetics of SPRC (20 mg/kg) in beagle dogs after oral and intravenous administrations were investigated in this study. Plasma concentrations of SPRC were measured by a LC-MS/MS method. Intravenous administration of SPRC (single dose) to beagle dogs gave a mean plasma half-life of 14.7 h, mean clearance of 0.4 ml min⁻¹ kg⁻¹ and mean apparent volume of distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A previous study indicated that H 2 S-releasing diclofenac derivatives, a novel class of non-steroidal anti-inflammatory drugs (NSAIDs), may be of clinical value in the treatment of osteolytic bone disease (35). In addition, preclinical studies have indicated that the novel hydrogen sulfide-modulating agent, S-propargyl-L-cysteine (SPRC) is a potent cardioprotective candidate (36). Our study provides a novel therapeutic role for H 2 S, which protects against HUVEC senescence.…”
Section: A B Cmentioning
confidence: 99%
“…A previous study indicated that H 2 S-releasing diclofenac derivatives, a novel class of non-steroidal anti-inflammatory drugs (NSAIDs), may be of clinical value in the treatment of osteolytic bone disease (35). In addition, preclinical studies have indicated that the novel hydrogen sulfide-modulating agent, S-propargyl-L-cysteine (SPRC) is a potent cardioprotective candidate (36). Our study provides a novel therapeutic role for H 2 S, which protects against HUVEC senescence.…”
Section: A B Cmentioning
confidence: 99%
“…Pharmacokinetic study plays an important role in the early stage of the development of new drugs [ 11 ]. The failure of drug development is to a certain extent attributed to the poor pharmacokinetic properties, such as low bioavailability or low metabolic stability [ 12 ]. So far, some studies for pharmacokinetic profiles of several coumarins including oxypeucedanin after administration of the herb medicine ADR extract have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to SAC, SPRC serves as a substrate of CSE and increases endogenous H 2 S production. Compared with NaHS, SPRC is more chemically stable and releases H 2 S in a slower and more sustained manner, with a half-life of about 3 h in rats [ 17 ], and about 16 h in Beagle dogs [ 18 ]. As an H 2 S donor, SPRC elicits extensive regulation on pathological conditions.…”
Section: Introductionmentioning
confidence: 99%